Perancangan Jaringan Fiber to the Building pada Gedung Tokong Nanas dengan Multi Aplikasi - Nadhasya, Athallah Favianauvally; Usman, Uke Kurniawan; Hambali, Akhmad (eProceedings of Engineering, 2024)
Abstract - The world of telecommunications is growing rapidly and requires quality communication services. Network design aims to improve the range and quality of services by expanding the network efficiently. The needs of various lecture activities, Telkom University must provide maximum service at each point of the building by prioritizing parameters such as capacity, quality, and connectivity of data transmission. This research aims to implement a Fiber to the Building (FTTB) system in Tokong Nanas Building, Telkom University, using Next Generation Passive Optical Network (NGPON) technology to increase connectivity and data capacity in accordance with the needs of students and lecture activities. This implementation starts from Sentral Telepon Otomat (STO) Cijawura to Tokong Nanas Building through two resilience lines Pasar Kordon and Cikoneng. NGPON technology is used to improve network quality with appropriate Quality of Service (QoS) standards. Keywords- FTTB, NGPON, Optical fiber, Quality of Service.